Perfection of the functional readiness of high-qualified athletes in the process of preparation for international competitions - Svetlana Karaulova; Nikolai Malikov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to evaluate the effectiveness of using the program of building the training process in the preparatory period of the annual macrocycle for improving the functional fitness of the athletes of the Ukrainian national track and field team in preparation for major international competitions. Material & Methods: in the study participated highly qualified athletes aged 19-23 years, specializing in running for short distances (n=10) and have a sporting title MSU and MSIG. Results: it is shown that the introduction in the preparatory period of this program, taking into account the dynamics of the components of the functional fitness of the athletes and the nature of their correlation with the model characteristics, contributed to a significant improvement in all indicators of the functional preparedness of the examined athletes. At the end of the preparatory period, the deviation of these indicators from the model values was only 2-6%. Conclusion: the obtained results testified to the positive impact of the program on the overall level of fitness of high-qualified athletes in the process of preparation for major international competitions.